Hospital-Acquired Acute Kidney Injury in Older Patients: Clinical Characteristics and Drug Analysis - Liu, Wei; Lian, Xing-Ji; Chen, Yuan-Han; Zou, Yi-Ping; Lin, Jie-Shan; Wu, Yan-Hua; Yu, Feng; Hu, Wen-Xue; Hao, Wen-Ke (Gerontology (Basel), 2022)
Information on older patients with hospital-acquired acute kidney injury (HA-AKI) and use of drugs is limited. This study aimed to assess the clinical characteristics, drug uses, and in-hospital outcomes of hospitalized older patients with HA-AKI. Patients aged ≥65 years who were hospitalized in medical wards were retrospectively analyzed. The study patients were divided into the HA-AKI and non-AKI groups based on the changes in serum creatinine. Disease incidence, risk factors, drug uses, and in-hospital outcomes were compared between the groups. Of 26,710 older patients in medical wards, 4,491 (16.8%) developed HA-AKI. Older patients with HA-AKI had higher rates of multiple comorbidities and Charlson Comorbidity Index score than those without AKI (p < 0.001). In the HA-AKI group, the proportion of patients with prior use of drugs with possible nephrotoxicity was higher than that of patients with prior use of drugs with identified nephrotoxicity (p < 0.05). The proportions of patients with critical illness, use of nephrotoxic drugs, and the requirements of intensive care unit treatment, cardiopulmonary resuscitation, and dialysis as well as in-hospital mortality and hospitalization duration and costs were higher in the HA-AKI than the non-AKI group; these increased with HA-AKI severity (all p for trend <0.001). With the increase in the number of patients with continued use of drugs with possible nephrotoxicity after HA-AKI, the clinical outcomes showed a tendency to worsen (p < 0.001). Moreover, HA-AKI incidence (adjusted odds ratio [OR], 10.26; 95% confidence interval (CI), 8.27-12.74; p < 0.001), and nephrotoxic drugs exposure (adjusted OR, 1.76; 95% CI, 1.63-1.91; p < 0.001) had an association with an increased in-hospital mortality risk. AKI incidence was high among hospitalized older patients. Older patients with HA-AKI had worse in-hospital outcomes and higher resource utilization. Nephrotoxic drug exposure and HA-AKI incidence were associated with an increased in-hospital mortality risk.